A Frontier 2D Nanobattery: â€œImproving Challenges (Hotumese) and Developmentâ€ - Hendry Izaac Elim; MogalahalliVenkatesh Venkatashamy Reddy; Rajan Jose (SCIENCE NATURE, 2019)
A brief conceptual challenges improvement (hotumese) and development of nanobattery is explained in a wide insight of intuition idea and technology planning for a better future human kind life particularly in their needs of mobile effective energy.